Diabetes Mellitus and Oxidative Stress. - Nilgün Altan (De Gruyter, 2006)
Oxidative stress in diabetes mellitus may play an important role in the pathogenesis of early and long term complications of hu human diabetes, like microangiopathy and neuropathy. Protein glycation and glucose autoxidation can generate free radicals that can catalyze lip ipid peroxidation. Other potential mechanisms of oxidative stress include the reduction of anti-oxidant defense. e. In this paper, the free radicals and anti-oxidant s t system a m are d e discussed.